Praktik Jurnalisme Kloning di Kalangan Wartawan Online - Tsana Garini; Abie Besman (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
The practice of cloning journalism is one of the most interesting phenomenon in the world of journalism. This practice has been considered as a common thing among journalists, especially online journalists. Whereas the practice of cloning journalism is closely related to plagiarism which is clearly incompatible with the ethics of journalism. Through this research the writer will discuss about the reasons behind this practice and what ethics have been violated by journalists who did it. The writer also discuss what ethics have been violated by journalists who do cloning journalism and why is this practice rife among online journalists using an autoetnography research method. The result of this research shows that the practice of cloning journalism among journalists is done because of several factors that include cooperation and solidarity among fellow journalists, the demand of online journalists’ work to write as many news as possible in the shortest period of time, the performance of journalists as an individual, regulation of mass media company, and the development of technology. The practice of cloning journalism is proven to be incompatible with the ethics of journalism because it is a form of plagiarism in the realm of mass media. It is also incompatible with regulations about accuracy and verification.